Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm having some trouble deriving a generalization for $\sigma_\alpha(n)$ from this: $$\sigma_1(n)=\sum_{d \mid n} \varphi(d)\sigma_0 \left( \frac{n}{d} \right).$$ My proof of the above is $$\sigma_1=N \ast u = (\varphi \ast u) \ast u = \varphi \ast (u \ast u) = \varphi \ast \sigma_0,$$ and by experimentation I found $$\sigma_\alpha(n)=\sum_{d \mid n} \varphi(d^\alpha)\sigma_{\alpha-1} \left( \frac{n}{d} \right),$$ but I don't see how I can derive this from $\sigma_\alpha=N^\alpha \ast u$. I don't even know how to write the $\varphi(d^\alpha)$-part... Am I doing this all wrong or is it just some detail I'm missing?

share|cite|improve this question
To put anon's comment another way: what exactly were you Dirichlet-convolving? – J. M. Oct 25 '11 at 9:58
@anon: Oh, ok, I'm using the notation as it is presented in Apostol. $N=\text{Id}$ and $u=1$, using the notation from link – Carolus Oct 25 '11 at 9:59
up vote 7 down vote accepted

Alternatively, a purely functional approach might go like $$\rm\sigma_\alpha=(\color{Blue}{Id}\cdot Id^{\alpha-1})*1 \tag{1}$$ $$\rm= (\color{Blue}{(\varphi*1)}\cdot\color{Red}{Id^{\alpha-1}})*1 \tag{2}$$ $$\rm=(\color{Orange}(\color{Red}{Id^{\alpha-1}}\cdot\color{Blue}{\varphi}\color{Orange})*\color{Red}{Id^{\alpha-1}})*1 \tag{3}$$ $$\rm =\color{Orange}(\color{Green}{Id^{\alpha-1}\cdot\varphi}\color{Orange})*(\color{Purple}{Id^{\alpha-1}*1}) \tag{4}$$ $$\rm=(\color{Green}{\varphi\circ Id^\alpha})*\color{Purple}{\sigma_{\alpha-1}}. \tag{5}$$ In the above we used

  • $\rm\color{Purple}{\sigma_\alpha}=\color{Purple}{Id^\alpha*1}$ in $\rm(1),\;(4)\to(5)$ by definition.
  • $\rm \color{Blue}{Id}=\color{Blue}{\varphi*1}$ from $\rm(1)\to(2)$.
  • $\rm Id^\rho$ is completely multiplicative for any $\rho$, in $\rm(2)$.
  • $(\color{Blue}{g*h})\cdot\color{Red}f=(\color{Blue}g\cdot \color{Red}f)*(\color{Blue}h\cdot\color{Red}f)$ when $f$ is completely multiplicative, from $\rm(2)\to(3)$.
  • Associativity, $(\color{Orange}a*b)*c=\color{Orange}a*(b*c) $, from $\rm(3)\to(4)$.
  • $\rm \color{Green}{Id^{\rho-1}\cdot\varphi}=\color{Green}{\varphi\circ Id^{\rho}}$ from $\rm(4)\to(5)$.
share|cite|improve this answer
I believe this is precisely what I was looking for! – Carolus Oct 25 '11 at 11:04
Very well explained! Thanks again! – Carolus Oct 25 '11 at 11:19
+1 for pretty colors – Greg Martin Nov 4 '11 at 19:15

We define $$\sigma_{x}(n)=\sum_{d|n} d^x,$$ so that $\sigma_x = 1*N^x.$ This means that it has the Dirichlet series $\zeta(s-x)\zeta(s)$. Your identity is correct, the simplest way to prove it is perhaps with Dirichlet series. Notice that $\phi(d^\alpha)=d^{\alpha-1}\phi(d)$ so that $\sum_{d|n}\phi(d^\alpha)\sigma_{\alpha-1}\left(\frac{n}{d}\right)$ are the Dirichlet coefficients of the series $$\left(\sum_{n=1}^\infty \frac{\phi(n)}{n^{s-\alpha+1}}\right)\left(\sum_{m=1}^\infty \frac{\sigma_{\alpha-1}}{n^s}\right)$$ As the series for the Totient function is $\frac{\zeta(s-1)}{\zeta(s)}$ this becomes $$= \frac{\zeta(s-\alpha)}{\zeta(s-\alpha-1)}\cdot \zeta(s-\alpha-1)\zeta(s)=\zeta(s-\alpha)\zeta(s). $$

Now this is the dirichlet series for $\sigma_a(n)$, so we have proven the identity.

share|cite|improve this answer
Thanks, but I'm sorry to say I've never seen Dirichlet series before. Is it possible to do this using the same (or a similar) method as the one I used to prove $\sigma_1$? – Carolus Oct 25 '11 at 10:09
@Carolus: if you're familiar with combinatorics, what Eric did here is more or less taking the generating function approach to proving identities. – J. M. Oct 25 '11 at 10:13
@J.M.: sorry, I've just started looking at combinatorics, I haven't seen generating functions yet :/ Thanks though, since I'm self studying mathematics, comments like this can be very helpful! – Carolus Oct 25 '11 at 10:17

Also you can use Exercise 2.17 on p48 (Apostol) where the Jordan totient $J_k(n)$ is defined.

Then $J_{\alpha}=\mu*N^\alpha$ so $\sigma_{\alpha}=J_{\alpha}*\sigma_{0}$ - perhaps a more pleasing generalisation.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.